Smartlock Trolley / Khairunnisa Ahmad Kamaruddin - Ahmad Kamaruddin, Khairunnisa (2020)
Nowadays, most advanced technology is demanded by people and industries all over the world for various purposes as it saves their time, energy and make their life easier. Thus, an idea of innovation was introduced to improve the current shopping trolley in the market. Shoppster Trolley Sdn. Bhd. introduce an innovation of shopping trolley that uses fingerprint lock buckle seat belt named Smartlock Trolley. The objectives of this product is to reduce the injured cases and increase the safeness of the kids while using the shopping trolley. Smartlock Trolley is easy to use and convenience for the users since it helps the customers to handle the kids while shopping. It replaces the push buckle seat belt with fingerprint lock buckle seat belt to improve the existing shopping trolley in the market. The fingerprint lock buckle seat belt uses a biometric capacitive fingerprint sensor scanner as a lock that attaches at the 5-points harness seat belt. It is to prevent the kids from unbuckling the seat belt by itself and exposes to the high rate of injury. Additionally, Smartlock Trolley also provides a child seat that can be adjusted as it gives more space and comfort. The price of the Smartlock Trolley is estimates RM 720 per unit. It is affordable as it uses high technology and high quality of materials. Hence, with these innovations of Smartlock Trolley, it can attract the potential customer to purchase the product.